2003
DOI: 10.1046/j.1365-313x.2003.01678.x
|View full text |Cite
|
Sign up to set email alerts
|

Module‐specific regulation of the β‐phaseolin promoter during embryogenesis

Abstract: SummaryThe phas promoter displays stringent spatial regulation, being very highly expressed during embryogenesis and completely silent during all phases of vegetative development in bean, Phaseolus vulgaris. This pattern is maintained in transgenic tobacco and, as shown here, Arabidopsis. Dimethyl sulphate in vivo footprinting analyses revealed that over 20 cis-elements within the proximal 295 bp of the phas promoter are protected by factor binding in seed tissues whereas none are bound in leaves. The hypothes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
106
0

Year Published

2003
2003
2017
2017

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 92 publications
(111 citation statements)
references
References 70 publications
(126 reference statements)
5
106
0
Order By: Relevance
“…2, histochemical staining patterns for embryos harboring mTATA1-gus (B) or mTATA2-gus (C) were similar to that obtained for embryos bearing the Ϫ295phas-gus control (A). The absence of GUS expression in the radicle is consistent with earlier findings that expression in this region is mediated by distal regulatory elements upstream of bp Ϫ295 (14). As with Ϫ295phas-gus control plants, no GUS expression could be detected in leaves of the stably transformed Arabidopsis plants harboring the TATA mutants (data not shown).…”
Section: Multiple Tata Elements Are Not Essential For Spatial Expresssupporting
confidence: 91%
See 2 more Smart Citations
“…2, histochemical staining patterns for embryos harboring mTATA1-gus (B) or mTATA2-gus (C) were similar to that obtained for embryos bearing the Ϫ295phas-gus control (A). The absence of GUS expression in the radicle is consistent with earlier findings that expression in this region is mediated by distal regulatory elements upstream of bp Ϫ295 (14). As with Ϫ295phas-gus control plants, no GUS expression could be detected in leaves of the stably transformed Arabidopsis plants harboring the TATA mutants (data not shown).…”
Section: Multiple Tata Elements Are Not Essential For Spatial Expresssupporting
confidence: 91%
“…Plasmid Constructions-Promoter fragments bearing mutations in the TATA region were digested with HindIII and NcoI, and ligated to HindIII/NcoI-digested vector Ϫ295phas-gus-3Ј/pUC (14). Subsequently, the constructs were digested with HindIII and EcoRI to release fragments containing the mutant Ϫ295phas promoter, reporter gene and the 3Ј region.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Research in several laboratories with legume seed protein genes, such as b-conglycinin, glycinin, Kunitz trypsin inhibitor, and lectin, showed that their mRNA accumulation patterns are regulated temporally and spatially (Goldberg et al, 1981a(Goldberg et al, , 1983Meinke et al, 1981;Rerie et al, 1992) and controlled by both transcriptional and posttranscriptional processes (Evans et al, 1984;Beach et al, 1985;Chappell and Chrispeels, 1986;Walling et al, 1986). Subsequent work determined that cisregulatory sequences flanking legume seed protein genes could confer embryo-specific expression patterns in heterologous plants, such as tobacco (Nicotiana tabacum) and petunia (Petunia hybrida; Chen et al, 1986;Okamuro et al, 1986;Jofuku et al, 1987;Higgins et al, 1988;Naito et al, 1988;Baumlein et al, 1992;Wohlfarth et al, 1998;Chandrasekharan et al, 2003).…”
Section: Legumes Have Been Used To Study Seed Development For More Thmentioning
confidence: 99%
“…Activation of downstream genes is mediated by specific binding of the B3 domain (Suzuki et al, 1997;Kroj et al, 2003;Carranco et al, 2004;Monke et al, 2004;Braybrook et al, 2006) to the Sph/RY cis-element (Hattori et al, 1992;Kao et al, 1996;Ezcurra et al, 1999;Reidt et al, 2000;Chandrasekharan et al, 2003;Nag et al, 2005). In addition, ABI3 mediates ABA-regulated gene expression in the seed through interaction with specific basic Leu-zipper transcription factors that bind ABA response elements (Finkelstein et al, 2002).…”
mentioning
confidence: 99%